Response Of Latheticus oryzae (Coleoptera: Tenebrionidae) To Three Pyrethroid Insecticides - Lubna Y. Abbass (College of Education for Pure Sciences, 2008)
Laboratory experiments were carried out to evaluate the response of 4th and 6th larval instars and 1week old adults Latheticus oryzae by exposure for 24, 48, and 72 hour to wheat treated with different concentrations of the three pyrethroids: ALPHACHEM® (5 EC), TRUST® (25 WP) and DECIS® (20 EC). Based on the Lc50 values of the three insecticides the result showed that 4th instar larvae were much susceptible to the insecticides than the 6th instar larvae and adults. The toxicities of insecticides increased (the values of Lc50 decreased ) as the exposure period increased from 24 to 72 hour. Also th study showed that, ALPHACEM and DECIS were more effective than TRUST.